POLA PENGASUHAN ORANG TUA GENERASI Z TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI (5-6 TAHUN) - Amelia Listianti Putri 10030222010 (Bandung Conference Series: Early Childhood Teacher Education, 2026)
Abstract. Generation Z parents grew up in the digital era and bring a different parenting approach than previous generations, particularly in supporting the social-emotional development of early childhood. This study aims to examine the social-emotional parenting patterns implemented by Generation Z parents toward early childhood (5-6 years old) at RA Al-Islamiyah, Bandung Regency. The study used a descriptive qualitative approach with a case study method. Data were collected through semi-structured interviews with four Generation Z parents and two classroom teachers, direct observation, and documentation of learning activities. The results show: (1) the main values underlying parenting are empathy and role modeling, while the parenting principles include open communication, positive discipline, mindful parenting, and active parental involvement; (2) forms of implementation include emotion coaching, dialogue-based discipline, active involvement, technology mediation (digital parenting), behavioral modeling, and mindful parenting; (3) the main obstacles are inconsistency in parenting practice, poorly controlled technology use, and social pressure from digital media, while the efforts to overcome them include improving parenting literacy, wise digital parenting, open communication, and strengthening emotional involvement. Overall, the children's social-emotional development ranges from Beginning to Developing as Expected, indicating a positive impact of Generation Z parenting patterns. Keywords: Parenting Patterns, Generation Z Parents, Social-Emotional Development, Early Childhood. Abstrak. Orang tua Generasi Z tumbuh di era digital dan membawa pendekatan pengasuhan yang berbeda dari generasi sebelumnya, khususnya dalam menunjang perkembangan sosial emosional anak usia dini. Penelitian ini bertujuan mengkaji pola pengasuhan sosial emosional yang diimplementasikan oleh orang tua Generasi Z terhadap anak usia dini (5-6 tahun) di RA Al-Islamiyah Bandung. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus. Pengumpulan data dilakukan melalui wawancara semi-terstruktur kepada empat orang tua Generasi Z dan dua guru kelas, observasi langsung, serta dokumentasi kegiatan pembelajaran. Hasil penelitian menunjukkan: (1) nilai utama yang melandasi pengasuhan adalah empati dan keteladanan, sedangkan prinsip pengasuhan mencakup komunikasi terbuka, disiplin positif, mindful parenting, dan keterlibatan aktif orang tua; (2) bentuk penerapan pengasuhan meliputi pendampingan emosi, disiplin berbasis dialog, keterlibatan aktif, mediasi teknologi (digital parenting), keteladanan perilaku, dan pengasuhan sadar; (3) hambatan utama mencakup ketidakkonsistenan pola asuh, penggunaan teknologi yang kurang terkontrol, dan tekanan sosial dari media digital, serta upaya mengatasinya meliputi peningkatan literasi parenting, penerapan digital parenting yang bijak, komunikasi terbuka, dan penguatan keterlibatan emosional. Secara keseluruhan, perkembangan sosial emosional anak berada pada rentang Mulai Berkembang hingga Berkembang Sesuai Harapan, yang mengindikasikan dampak positif pola pengasuhan orang tua Generasi Z. Kata Kunci: Pola Pengasuhan, Orang Tua Generasi Z, Sosial Emosional, Anak Usia Dini.